Pemanfaatan Aplikasi Media Sosial sebagai Media Promosi UMKM pada Warung Cik Pen di Pantai Tok Anjang, Kecamatan Nongsa, Kota Batam - Surahaman hakim; Ahmad Muh Yusran AA; Faisa Enjelita Busri; Nabila Nabila; Nazurah Nur Rizkal; Aprilia Ananda Harbi; Reyaldi Syaki Maulana; Mefri Yudi Wisra; Andi Muamar (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting Indonesia's economic growth. However, many MSMEs have not optimally utilized digital technology as a promotional medium. One of them is Warung Cik Pen, located at Tok Anjang Beach, Nongsa District, Batam City, whose promotional activities relied mainly on word of mouth marketing. This community service program aimed to improve the owner's knowledge and skills in utilizing social media as a digital marketing tool. The program was conducted for 30 days using observation, interviews, socialization, training, mentoring, and evaluation methods. The activities included training on digital marketing, Instagram Business, Facebook Page, WhatsApp Business, Google Maps, and Canva for creating promotional content. The results showed an improvement in the owner's ability to manage social media independently. The outputs included promotional banners, redesigned menus, optimized social media accounts, a WhatsApp Business product catalog, business location registration on Google Maps, and digital promotional content. These outcomes are expected to expand market reach and improve the competitiveness of Warung Cik Pen as a local culinary MSME.